Tobacco, Alcohol and Drug Use among Dental Undergraduates at One UK University in 2015 - James Puryer; Rebecca Wignall (MDPI AG, 2016)
The aim of this study was determine the prevalence of tobacco, alcohol and illicit substance use among dental undergraduates at one UK university in 2015. A cross-sectional survey of all 344 dental undergraduates using an anonymous self-report questionnaire was carried out. The response rate was 77%, of which 29% were male and 71% female. Tobacco smoking was reported by 23.6% of males and 12.2% of females, with only 1.6% of females reporting to smoke ≥10 cigarettes per day. Alcohol consumption was reported by 85.5% of males and 84% of females, and reported levels of alcohol consumption increased since becoming undergraduates. Binge drinking was reported by 35.3% of males and 41% of female students. Only 2.6% of males and 0.5% of females reported to be current regular users of cannabis. The vast majority of respondents claimed to have never used any illicit substance. The only other reported regularly used substances by males was Ecstasy (1.3%) and by females were LSD (0.5%), Ecstasy (1.5%), Cocaine (0.5%), Inhalants (0.5%) and Ketamine (0.5%). These results are encouraging. Fewer students reported smoking than in the general population, levels of binge drinking were considerably lower than previously reported figures, as were the numbers of regular users of cannabis and other illicit substances.